Combustion Characteristics of Horizontal Diesel Spray Burner in Low-Pressure Chamber Based on Multivariate Correlation Analysis - Kai Xie; Yunjing Cui; Xingqi Qiu; Jianxin Wang (Complexity)
At present, the burning problem of low power burners widely used in emergency and stove heating on the plateau has gradually attracted people’s attention. The fuel injection pressure, inlet air flow, air distribution regulation coefficient, and environmental pressure were considered respectively, and then the four factors and six levels of a uniform experimental investigation were conducted in a low-pressure chamber with adjustable atmospheric pressure. The flame morphology, flame temperature, and NO emission were investigated, and their correlation with each independent variable was analyzed. In addition, burning of droplet swarm was obtained with the simulate numerical calculation by the ANSYS FLUENT. The results showed that the low-pressure environment had a negative correlation with the maximum width and position of flame, the characteristics of flame uplifted and NO emission. Air volume determines the length of the flame, and atmospheric pressure and fuel injection pressure determine the maximum width of the flame. The shape of the horizontal jet flame in plateau environment is more dependent on the regulation of air volume. In order to reduce NO emission in plateau environment, it may be necessary to maintain a large air supply volume and reduce fuel injection pressure appropriately. At the microscopic level of droplet combustion, change mechanisms of macro flame shape in different sub-atmosphere were analyzed. The mechanism of flame morphological change in the plateau environment is the increase in droplet burning time and path. The adjustment of flame under sub-atmospheric pressure through the change of operating parameters is essential to improve the burning rate of droplets.